Pengaruh Kepribadian Proaktif terhadap Perilaku Inovatif, Komitmen Afektif, dan Kesejahteraan Kerja - Rahmawati, Ega (Universitas Negeri Surabaya, 2024)
The era of globalization has brought major changes in organizations. Organizations need human resources with a very proactive personality to make changes that benefit the organization. Therefore, having a proactive personality is very important for a teacher. Teachers with a very proactive personality will act actively to improve teaching conditions and overcome any challenges of change that impact the quality of their work. Proactive personality itself has an impact on innovative behavior, affective commitment, and work well-being. This research aims to analyze proactive personality having a positive and significant influence on innovative behavior, proactive personality having a positive and significant influence on affective commitment, and proactive personality having a positive and significant influence on work well-being. For this reason, this research topic is SMAN 1 Babat, and the subject is the teacher. The number of respondents in this study was 93, distributing questionnaires directly. Quantitative methods with primary data sources will be used in this research. The sampling technique uses random sampling. Statistical analysis of the research used Structural Equation Modeling on SmartPLS software version 3. The research results explained that proactive personality had a positive and significant effect on innovative behavior, proactive personality had a positive and significant effect on affective commitment, and proactive personality had a positive and significant effect on work well-being. This research can be a reference for the principle of SMAN 1 Babat in increasing innovative behavior, affective commitment, and work well-being.